2012
DOI: 10.1177/0300985812461362
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Binding of Beta Toxin to Small Intestinal Mucosal Endothelial Cells in Early Stages of Experimentally Induced Clostridium Perfringens Type C Enteritis in Pigs

Abstract: Beta toxin (CPB) is known to be an essential virulence factor in the development of lesions of Clostridium perfringens type C enteritis in different animal species. Its target cells and exact mechanism of toxicity have not yet been clearly defined. Here, we evaluate the suitability of a neonatal piglet jejunal loop model to investigate early lesions of C. perfringens type C enteritis. Immunohistochemically, CPB was detected at microvascular endothelial cells in intestinal villi during early and advanced stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 12 publications
1
28
1
Order By: Relevance
“…Histologically, the hallmark of type C infection is necrosis of the intestinal wall, which starts in the mucosa but usually progresses to affect all layers of the intestine. Fibrin thrombi occluding superficial arteries and veins of the lamina propria and submucosa are characteristic of this condition (207), and it was postulated (although not yet definitely proven) that vascular damage by CPB is an early event in type C infections (211,212).…”
Section: Diseases Involving Primarily Plasmid-encoded Toxinsmentioning
confidence: 99%
“…Histologically, the hallmark of type C infection is necrosis of the intestinal wall, which starts in the mucosa but usually progresses to affect all layers of the intestine. Fibrin thrombi occluding superficial arteries and veins of the lamina propria and submucosa are characteristic of this condition (207), and it was postulated (although not yet definitely proven) that vascular damage by CPB is an early event in type C infections (211,212).…”
Section: Diseases Involving Primarily Plasmid-encoded Toxinsmentioning
confidence: 99%
“…The toxin forms pores in cells and in bilayer lipid membranes, creating channels that induce K + efflux and Ca 2+ , Na + and Cl − influxes, which are responsible for cell swelling and lysis (Nagahama et al, 2003). It has been shown to bind to intestinal endothelial cells, a fact that has been hypothesized to be an early step in endothelial cell necrosis, leading to thrombosis and ultimately intestinal necrosis (Miclard et al, 2009a and b; Schumacher et at, 2013). It has been recently demonstrated that CPB induces necrotic cell death in porcine endothelial cells in vitro, which is associated with an increase in intracellular calcium and is inhibited by necrostatin-1, suggesting a programmed cell necrosis (necroptosis) mechanism (Autheman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…C. perfringens type C disease has been studied using several animal models including pigs, sheep, goats, rabbits, guinea pigs, and mice (Field and Goodwin, 1959; Kohler et al, 1979; Lawrence and Cooke, 1980; Johansen et al, 1986a,b,c; Sayeed et al, 2008; Uzal et al, 2009; Garcia et al, 2013; Schumacher et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to confirm that the endothelium is the target cell of perfringolysin or alpha toxin in bovine necrohemorrhagic enteritis, it would be interesting to localize the toxin in lesions, as already been done for beta toxin in necrotic enteritis in piglets and in a human case [31,32]. Beta toxin has been shown to induce porcine endothelial cell damage in vitro and to bind to endothelial cells, and not to epithelial cells, in the gut of diseased animals, suggesting that disruption of endothelial cells plays a role in type C enteritis [30,31,33]. …”
Section: Discussionmentioning
confidence: 99%